Effect of a Nurse-Led Teaching Program on Sleep Disturbances and Pain Experiences Among Patients With Fibromyalgia - Aziza Ibrahim Abd El Kader PhD; Rasha Hafez Ramadan El-Shaboury PhD; Rehab Fouad Abd Elkodoos PhD; Hend Reda Ali Elkest PhD; Nermen Abdelftah Mohamed PhD (SAGE Open Nursing)
Introduction Fibromyalgia is a chronic condition causing widespread pain in the muscles and bones, frequently occurring alongside fatigue, sleep problems, cognitive difficulties, and mood disorders. Objective This study investigates the effectiveness of a nurse-led teaching program on sleep disturbances and pain experiences among patients with fibromyalgia. Methods A quasi-experimental with pretest and posttest measures was implemented in this study. Sixty patients with fibromyalgia were included in the sample, divided equally into a study group and a control group (30 patients each). The study took place at the rheumatology outpatient clinic of Mansoura University Hospital, Egypt from June 1, 2024, to December 31, 2024. The program consisted of 24 consecutive sessions, each lasting ∼20–30 min for 12 weeks. Researchers used three tools to collect data; Demographics Form, Visual Analogue Scale (VAS), and the Pittsburgh Sleep Quality Index (PSQI). Results The two groups exhibited no statistically significant differences. across all demographic characteristics ( p  > .05), except for place of residence ( p  = .0383). Prior to the program, independent samples t -tests revealed that there were no statistically significant differences in mean PSQI and VAS scores between the two groups. However, after the program, there was a statistically significant difference in mean PSQI scores ( p  = .009) and VAS scores ( p  = .05) between groups. Conclusion A nurse-led teaching program can be a valuable nonpharmacological intervention for managing sleep disturbances and pain in patients with fibromyalgia, highlighting the crucial role of nurses in empowering patients with self-management strategies.